Effect of Acupuncture Therapy on Pain Reduction in Dysmenorrhea Patients: A Meta-Analysis - Novitasari, Elisa; Soemanto, RB; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Dysmenorrhea is a common com